Reliability evaluation of radial distribution system considering common mode failures and different weather effects - Bhargava Chitumodhu; Gangaraju Pilly (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
Reliability evaluation of distribution systems plays a crucial role in ensuring the uninterrupted supply of electricity to consumers. This paper presents a comprehensive analysis of distribution system reliability using the Failure Mode and Effects Analysis (FMEA) technique. The study focuses on evaluating the reliability of the distribution system considering various failure modes, including busbar failure, section failure, distributor failure, transformer failure, maintenance-related issues, transient failures, and the impact of weather conditions. The findings of this research can assist utilities and system operators in identifying critical failure modes and implementing appropriate measures to enhance the reliability of distribution systems, ensuring continuous and reliable electricity supply to consumers.